PERBANDINGAN HUKUM PERATURAN INSIDER TRADING DALAM TINDAK PIDANA PASAR MODAL DI INDONESIA DAN SINGAPURA - Iqbal, Nada (Universitas Ekasakti, 2023)
Information Disclosure and Investors are very important parties in capital market activities. However, in the event of a violation of capital market regulations, namely the crime of insider trading, which can be carried out by various parties for personal gain, this violates the principle of fair securities trading. This research focuses on the classification of criminal acts in the capital market in Indonesia and a comparison of legal regulations regarding insider trading in Indonesia and Singapore. In this study, normative legal research was used and the nature of the research conducted by the author was an analytical descriptive study. After conducting research, it was found that the concept contained differences in regulations regarding insider trading between Indonesia and Singapore, one of which was that Indonesia adhered to the theory of Fiduciary Duty while Singapore adhered to the theory of Fiduciary Duty and Misappropriation Theory. This theory is a legal protection that is needed by Indonesian capital market investors at this time, but in the regulations there are still a number of things that need to be evaluated and further developed by the OJK so that when it is implemented later the goal of adopting the concept as a violation prevention effort can be achieved.